Use of satellite data to identify critical periods for early life survival of northern shrimp in the Gulf of Maine. (15th March 2016) - Richards, R. Anne; O'Reilly, John E.; Hyde, Kimberly J.W.
Abstract: The northern shrimp Pandalus borealis is at its southern limit in the Gulf of Maine (GOM), and recruitment success is higher in years with relatively cool water temperature. However, the mechanisms for the temperature effect are not clear. We used rolling window analysis of daily satellite data to identify critical periods for early life survival of the 1998–2012 northern shrimp year‐classes and to investigate the importance of the phenology of the hatch and bloom. Survival was negatively correlated with sea surface temperature (SST) during a 6‐week period around the time of larval emergence (late winter) and during a 4‐week period in late summer when SST and stratification reached annual maxima. Survival was negatively correlated with chlorophyll‐ a concentration (chl‐ a ) during two 5‐week periods centered approximately a month before the hatch midpoint and around the time of settlement to the benthos. A small‐magnitude winter bloom occurred around the time of the hatch in many years, but our results did not reveal a link between survival and bloom‐hatch phenology. The timing of winter and spring blooms were correlated with SST during the preceding 10 months. A survival model including SST and chl‐ a during the critical periods explained 73% of the variance in survival. Summer SST increased significantly during the study period; the other critical variables showed no trend. The rolling windows approach revealed sensitive periods in early life history that may not have otherwise been hypothesized, providing a foundation for research towards a greater understanding of processes affecting recruitment.